AN ANALYSIS OF DEIXIS IN PAMUNGKAS'S "ONE ONLY" SONG LYRICS - Siti Kusumadewi; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2020)
The aims of this research are to analyze the kinds of deixis that are used in One Only song lyrics and to find out the types of deixis that are major used in in the song lyrics. The researcher choose this song because this song is easy to listen to and got a good response from the listener. This research used qualitative research. The result of this research showed that in the One Only song lyrics there are four kinds of deixis, there are personal deixis, spatial deixis, temporal deixis and social deixis. Based on the discussion, personal deixis came as the most often appears deixis with 50 deictic words found or 92.6 %, the second is Spatial deixis (2 deictic words or 3.7 %), followed by temporal deixis and social deixis with the percentage of 1.85 % each. Keywords:        Deixis, Song Lyrics, Pamungkas